Pengaruh Program, Manajemen, dan Anggota terhadap Efektivitas Partisipasi pada Anggota Koperasi - Kadek Renita Dwi Aryanthi; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to examine the effect of programs, management, and members on the effectiveness of participation among cooperative members. The study employs a quantitative approach with a causal research design. The research data were collected through the distribution of questionnaires to 224 respondents selected from a population of 511 cooperative members using the Slovin formula with a proportional random sampling technique. The results show that (1) programs have an effect on the effectiveness of participation, (2) management has an effect on the effectiveness of participation, (3) members have an effect on the effectiveness of participation, and (4) programs, management, and members simultaneously affect the effectiveness of participation. The coefficient of determination indicates that 80% of the effectiveness of participation is influenced by these three variables, while the remaining 20% is influenced by other factors outside the scope of this study. Based on these findings, it is recommended that cooperatives improve the quality and relevance of their programs, strengthen management practices, and encourage member awareness and involvement in order to sustainably enhance the effectiveness of participation.